Silent threats on surfaces and equipment in the newborn unit of Kenyatta National Hospital in Kenya - Adut Malual; Anne Maina; Dennis Kithinji; Winnie Mutai (Microbes and Infectious Diseases, 2023)
Background: Contaminated hospital surfaces and equipment can serve as reservoirs for potentially pathogenic bacteria. They can contribute to persistent and silent transmission of infections. This study aimed to investigate the bacterial contamination and antimicrobial susceptibility patterns of potentially pathogenic bacteria isolated from surfaces and equipment in the newborn unit (NBU) of Kenyatta National Hospital (KNH). Methods: We conducted a cross-sectional study by sampling surfaces and equipment at NBU of KNH. A total of 580 swabs were collected from cots, incubators, radiant warmers, weighing scales, suction machines, oxygen masks, desk surfaces, door handles, keyboards, PC mouse, sinks, and taps. Culture of the swabs and isolation, identification and antimicrobial susceptibility testing of the isolates were performed using standard microbiological methods. Results: Growth was observed in 273 (54%) of the 580 swabs. Coagulase-negative staphylococcus (CoNS) were the most common contaminants, 137/273 (50.2%). Klebsiella pneumoniae (119/273, 43.6%), Escherichia coli (16/273, 5.9%), and Pseudomonas aeruginosa (P.  aeruginosa ) (1/273, 0.4%) were also isolated. The highest proportion of contaminants were found in cots (55/273, 20%), radiant warmers (51/273, 19%), oxygen masks (46/273, 17%), and desk surfaces (29/273, 11%). Antimicrobial resistance to penicillin, clindamycin, and vancomycin was observed in several isolates. Conclusion: Significant proportions of antibiotic-resistant contaminants were isolated from the NBU’s surfaces and equipment. The hospital should implement strict infection control measures and regularize monitoring and surveillance of hospital surfaces and equipment for potential antibiotic-resistant pathogens to prevent their persistence and silent transmission.